Desertia, a new genus in Massonieae (Asparagaceae, Scilloideae), including the description of Desertia luteovirens and the taxonomic revisions of Whiteheadia and Namophila - Martínez-Azorín, Mario; Pinter, Michael; Wetschnig, Wolfgang (Phytotaxa, 2015)
Desertia gen. nov., which belongs to tribe Massonieae, is described from south western Namibia and north western South Africa. Desertia is at first sight related to Whiteheadia and Massonia, but it can be clearly differentiated by the papillose bracts, subcampanulate flowers with straight, suberect or slightly spreading free portion of tepals and the rugose seeds. This genus is based on Whiteheadia etesionamibensis, for which the combination in Desertia is presented. Furthermore, a second species in the genus, D. luteovirens, is here described based on distinct morphological and molecular characters. Furthermore, taxonomic revisions are presented for Namophila and Whiteheadia, including identification keys for the three genera and data on morphology, ecology, and distribution for all accepted species.